Report of the Steering Committee on Voluntary Sector For The Tenth Five Year Plan (2002-2007) - Planning Commission (Planning Commission, Government of India, 2002)
The Report of the Steering Committee on the Voluntary Sector for the Tenth Five-Year Plan (2002–2007), constituted by the Planning Commission, provides a comprehensive examination of the historical evolution, diversity, and developmental significance of voluntary action in India, while outlining strategic measures to strengthen the sector’s role in national planning. Recognizing India’s deep-rooted traditions of charity, social reform, and community service shaped by religious institutions, social movements, and Gandhian philosophy, the report traces the expansion of voluntary organizations (VOs) and non-governmental organizations (NGOs) from welfare-oriented activities to multi-sectoral development interventions encompassing education, health, environment, human rights, gender justice, disaster relief, and advocacy. It highlights the increasing recognition of the voluntary sector across successive Five-Year Plans as a critical partner in participatory democracy, grassroots mobilization, and decentralized development, particularly through collaboration with Panchayati Raj Institutions and community-based groups. The report underscores both the comparative advantages of VOs—such as proximity to marginalized communities, flexibility, innovation, and capacity to mobilize local resources—and their challenges, including limited scale, procedural complexities, accountability concerns, and fragmented coordination. Emphasizing the need for simplification of procedures, enhanced transparency, monitoring mechanisms, capacity building, inter-sectoral partnerships, and revitalization of volunteerism, the Committee advocates the creation of an enabling environment that respects the independence of the voluntary sector while strengthening its institutional framework. By positioning the Planning Commission as the nodal agency for government–voluntary sector interface and promoting collaborative governance, the report envisions a more effective, accountable, and participatory development process during the Tenth Plan period, where civil society acts as a catalyst for social cohesion, empowerment, and inclusive growth.
Government of India Planning Commission January 2002
Keywords: Voluntary Sector Development; Tenth Five-Year Plan; Participatory Democracy; Civil Society Organizations; Non-Governmental Organizations; Social Mobilization; Inter-Sectoral Partnership; Capacity Building; Panchayati Raj Institutions; Planning Commission Of India; Volunteerism; Institutional Reform